Contrasting expression pattern of RNA-sensing receptors TLR7, RIG-I and MDA5 in interferon-positive and interferon-negative patients with primary Sjögren's syndrome. Issue 4 (26th September 2016) - Maria, Naomi I; Steenwijk, Eline C; IJpma, Arne S; van Helden-Meeuwsen, Cornelia G; Vogelsang, Petra; Beumer, Wouter; Brkic, Zana; van Daele, Paul L A; van Hagen, P Martin; van der Spek, Peter J; Drexhage, Hemmo A; Versnel, Marjan A
Abstract : Objective: The interferon (IFN) type I signature is present in over half of patients with primary Sjögren's syndrome (pSS) and associated with higher disease-activity and autoantibody presence. Plasmacytoid dendritic cells (pDCs) are considered as the main source of enhanced IFN type I expression. The objective of this study was to unravel the molecular pathways underlying IFN type I bioactivity in pDCs of patients with pSS. Methods: Blood samples from 42 healthy controls (HC) and 115 patients with pSS were stratified according to their IFN type I signature. CD123 + BDCA4 + pDCs and CD14 + monocytes were isolated from peripheral blood mononuclear cells (PBMCs). Genome-wide microarray analysis was conducted on sorted pDCs in a small sample set, followed by validation of differentially expressed genes of interest in pDCs and monocytes. Results: We found an upregulation of endosomal toll-like receptor (TLR) 7, but not TLR9, in IFN-positive (IFNpos) pDCs (p<0.05) and monocytes (p=0.024). Additionally, the downstream signalling molecules MyD88, RSAD2 and IRF7 were upregulated, as were the cytoplasmic RNA-sensing receptors DDX58/retinoic acid inducible gene-I (RIG-I) and IFIH1/melanoma differentiation associated gene-5 (MDA5). In vitro triggering of the TLR7-pathway in HC PBMCs induced upregulation of DDX58/RIG-I and IFIH1/MDA5, and downregulated TLR9. The upregulation of TLR7, its downstream signalling pathway, DDX58/RIG-I and IFIH1/MDA5 were confined to patients with IFN-positive pSS. IFN-negative patients had a contrasting expression pattern—TLR7 normal, and decreased TLR9, RIG-I and MDA5. Conclusions: Here we conclude a contrasting expression pattern of the RNA-sensing receptors TLR7, RIG-I and MDA5 in pDCs and monocytes of patients with IFNpos pSS. This profile could explain the pathogenic IFN production and might reveal novel therapeutic targets in these patients.